Virtual Twin For Testbed Industr - Husák, Michal (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2020)
This article is based on my thesis. The main task was choosing the system, which will be able to virtual commissioning. Real hardware is tests bed for application of concept Industry 4.0. This machine can automatize barman process. It was chosen drink shaking cell for digital twin demonstration. Used software is Siemens NX with attached module Mechatronic Concept Designer.
Keywords: Industry 4.0; virtual commissioning; PLM; Mechatronic Concept Design; PLCSIM Advanced; Barman